2016
DOI: 10.1007/s00737-016-0618-4
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to access and utilization of eating disorder treatment among women

Abstract: Anorexia, bulimia, and other specified feeding or eating disorders (OSFED) are psychiatric disorders recognized in the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5). One difference of eating disorders compared to other psychiatric disorders is the physical effects of the disease. Although anorexia is easier to physically detect than bulimia and OSFED, many women remain undiagnosed and untreated. Even if an eating disorder is recognized by the individual, barriers to clinical diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 26 publications
1
39
1
4
Order By: Relevance
“…The reason for lack of disclosure and barriers to accessing health care treatment for eating disorders is similar among pregnancy and non-pregnant women. These include the severity of the health threat, the perception of the individuals’ eating disorder health, feelings of shame, stigma and the clinicians understanding and capacity to recognize an eating disorder [ 59 ]. While women with an eating disorder who are not pregnant may choose not to disclose and seek any medical treatment, pregnant women with an eating disorder are often already seeking care through a maternity care provider and may have frequent visits with a maternity care provider thus providing multiple potential opportunities for disclosure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for lack of disclosure and barriers to accessing health care treatment for eating disorders is similar among pregnancy and non-pregnant women. These include the severity of the health threat, the perception of the individuals’ eating disorder health, feelings of shame, stigma and the clinicians understanding and capacity to recognize an eating disorder [ 59 ]. While women with an eating disorder who are not pregnant may choose not to disclose and seek any medical treatment, pregnant women with an eating disorder are often already seeking care through a maternity care provider and may have frequent visits with a maternity care provider thus providing multiple potential opportunities for disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…As such, maternity care providers are in a unique position to provide an environment where pregnant individuals would feel comfortable disclosing their eating disorder. Maternity care providers could also help identify potential eating disorder behaviors, explain how serious eating disorders are especially during pregnancy and provide understanding and support [ 59 ]. Improving the eating disorder health literacy of maternal health care providers to be able to provide these services is an integral part of improving disclosure of an eating disorder during pregnancy and utilizing this opportunity to intervene [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stefl and Prosperi (1985) defined barriers to service use as involving multiple attributes: availability, accessibility, acceptability and affordability. A descriptive review of the literature published during the conduct of the present review identified key themes in barriers to care for eating disorders, such as personality traits, ethnicity and culture, health beliefs, physician beliefs, financial barriers, geographical barriers, and stigma (C. Thompson & Park, 2016). However, the identification of barriers within these studies has been largely dependent upon the method and focus of assessment.…”
Section: Assessing Treatment Barriers In Eating Disorders: a Systematmentioning
confidence: 98%
“…Within this framework, the authors propose as potential barriers personality traits (e.g., impulsivity, novelty seeking), health-related beliefs and affect (e. g., feelings of shame, the belief that those with an ED should help themselves), ethnicity/race (i.e., ethnic minority status), financial barriers (e.g., lack of health insurance coverage), physician misperceptions regarding the types of people who suffer from EDs, social stigma and guilt, and distance from treatment centers. While this paper (Thompson, & Park, 2016) presents a conceptual framework for understanding barriers, it does not include a systematic synthesis of all relevant research or analysis of individual study methodologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies to date have included a range of different variables, approaches, and samples, and hence have yielded largely inconsistent findings. In a recent review of barriers to ED treatment among women, Thompson and Park () used Andersen's Behavioral Model (Andersen, ) to summarize possible predisposing and enabling factors to the utilization of intensive outpatient or inpatient ED treatment. Within this framework, the authors propose as potential barriers personality traits (e.g., impulsivity, novelty seeking), health‐related beliefs and affect (e.g., feelings of shame, the belief that those with an ED should help themselves), ethnicity/race (i.e., ethnic minority status), financial barriers (e.g., lack of health insurance coverage), physician misperceptions regarding the types of people who suffer from EDs, social stigma and guilt, and distance from treatment centers.…”
Section: Introductionmentioning
confidence: 99%